2012
DOI: 10.1186/1472-6963-12-305
|View full text |Cite
|
Sign up to set email alerts
|

The work pattern of personal care workers in two Australian nursing homes: a time-motion study

Abstract: BackgroundThe aim of the study is to describe the work pattern of personal care workers (PCWs) in nursing homes. This knowledge is important for staff performance appraisal, task allocation and scheduling. It will also support funding allocation based on activities.MethodsA time-motion study was conducted in 2010 at two Australian nursing homes. The observation at Site 1 was between the hours of 7:00 and 14:00 or 15:00 for 14 days. One PCW was observed on each day. The observation at Site 2 was from 10:00 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…Previous studies 6,15,18 only presented the total direct care time, which was consistent with the first point presented above, but did not address the other points. The present study has advanced knowledge by providing more detailed information about each direct care activity.…”
Section: Common Findings At Both Racfssupporting
confidence: 73%
See 3 more Smart Citations
“…Previous studies 6,15,18 only presented the total direct care time, which was consistent with the first point presented above, but did not address the other points. The present study has advanced knowledge by providing more detailed information about each direct care activity.…”
Section: Common Findings At Both Racfssupporting
confidence: 73%
“…They reported that 30%-45% of a PC's time was spent on direct care in RACFs. 6,15,18 However, none of these studies reported how much time was allocated to each direct care activity in high-care RACFs. This limits the understanding about the time needed for meeting different care needs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Time-motion observation has been used by previous studies to evaluate the care processes in RACHs [11,12]. It requires an observer to follow one participant at a time and sequentially record the time taken for the person to conduct an activity, using a pre-defined activity classification system.…”
Section: Data Collection Methodsmentioning
confidence: 99%